Exploring the aftermath: Work demands, workplace violence, and job satisfaction among nurses in a public hospital in the post-COVID-19 era - Dita Sulistyowati; Hanny Handiyani; Moh Heri Kurniawan; Rahma Dwi Syukrini; Turyatiningsih (Belitung Raya Foundation, Indonesia, 2023)
Background: Despite the shift from the COVID-19 pandemic to an endemic phase, many individuals, including nurses, may still be facing psychosocial challenges after enduring three years of the pandemic. Although the anticipation that psychosocial issues, such as work demand and workplace violence, have diminished and nurses’ job satisfaction has improved, there is a scarcity of studies in Indonesia investigating this matter. Objective: This study aimed to 1) explore the current state of nurses’ work demands, workplace violence, and job satisfaction and 2) examine the relationships between work demands, workplace violence, and respondents’ characteristics with nurses’ job satisfaction. Methods: The study employed a cross-sectional survey design involving 247 nurses from a regional general hospital in Jakarta, Indonesia. Simple random sampling was used to select the participants, and the Copenhagen Psychosocial Questionnaire (COPSOQ) III was used for data collection. Data were analyzed using multiple linear regression. Results: The types of cognitive demands (M = 12.46, SD = 3.461), demands for hiding emotion (M = 11.66, SD = 3.554), and work pace (M = 9.87, SD = 2.847) scored an average close to or within the “sometimes/quite extensive” range on the scale. All types of workplace violence and conflicts occurred among nurses (Mean range = 1.21-2.57). Nurses perceived themselves as fairly satisfied with their job (M = 18.47, SD = 3.18). The results of the multiple linear regression indicated that nurses’ job satisfaction was predominantly influenced by workplace violence (β = -0.191), followed by the type of care unit (β = -0.167) and work demands (β = -0.126). These factors collectively accounted for 9.1% of the variance in the job satisfaction variable (R2 = 0.091, p <0.005) Conclusion: Despite the decreasing number of COVID-19 cases, nurses still experience high work demands and continue to face workplace violence. These factors, as well as the type of care unit, influence nurses’ job satisfaction. Therefore, further actions need to be taken by hospital management to address these psychosocial conditions. It is recommended that future research explore the role of nurse managers in managing the psychosocial factors associated with these three factors.